Advanced accounting : principles and procedural applications, vol. 1 - Guerrero, Pedro P.; Peralta, Jose F. (Manila, Philippines : GIC Enterprises & Co. Inc., 2017)
This 2017 edition of Advanced financial accounting contains 2 volumes and is designed for financial accounting courses above the intermediate level. The 2017 edition has been updated to reflect recent business developments and changes in accounting standards.
1. Partnership: Basic considerations and formation -- 2. Partnership Operations -- 3. Partnership Dissolution -- 4. Partnerships: Liquidation -- 5. Partnership: Liquidation by installment -- 6. Corporations in financial difficulty -- 7. Corporations ion financial difficulty: Reorganization and troubled debt restructuring -- 8. Installment sales -- 9. Long term construction contracts -- 10. Franchise accounting -- 11. Home office and branch accounting: General procedures -- 12. Home office and branch accounting: Special problems.
Keywords: ACCOUNTING